Mitochondrial genomes in Perkinsus decode conserved frameshifts in all genes - Gornik, Sebastian G.; Flores, Victor; Reinhardt, Franziska; Erber, Lieselotte; Salas-Leiva, Dayana E; Douvropoulou, Olga; Lassadi, Imen; Einarsson, Elin; Mörl, Mario; Git, Anna; Stadler, Peter F; Pain, Arnab; et al. (Molecular biology and evolution, 2022)
Mitochondrial genomes of apicomplexans, dinoflagellates, and chrompodellids that collectively make up the Myzozoa, encode only three proteins (Cytochrome b [COB], Cytochrome c oxidase subunit 1 [COX1], Cytochrome c oxidase subunit 3 [COX3]), contain fragmented ribosomal RNAs, and display extensive recombination, RNA trans-splicing, and RNA-editing. The early-diverging Perkinsozoa is the final major myzozoan lineage whose mitochondrial genomes remained poorly characterized. Previous reports of Perkinsus genes indicated independent acquisition of non-canonical features, namely the occurrence of multiple frameshifts. To determine both ancestral myzozoan and novel perkinsozoan mitochondrial genome features, we sequenced and assembled mitochondrial genomes of four Perkinsus species. These data show a simple ancestral genome with the common reduced coding capacity but disposition for rearrangement. We identified 75 frameshifts across the four species that occur as distinct types and that are highly conserved in gene location. A decoding mechanism apparently employs unused codons at the frameshift sites that advance translation either +1 or +2 frames to the next used codon. The locations of frameshifts are seemingly positioned to regulate protein folding of the nascent protein as it emerges from the ribosome. The cox3 gene is distinct in containing only one frameshift and showing strong selection against residues that are otherwise frequently encoded at the frameshift positions in cox1 and cob. All genes lack cysteine codons implying a reduction to 19 amino acids in these genomes. Furthermore, mitochondrion-encoded rRNA fragment complements are incomplete in Perkinsus spp. but some are found in the nuclear DNA suggesting import into the organelle. Perkinsus demonstrates further remarkable trajectories of organelle genome evolution including pervasive integration of frameshift translation into genome expression.
Gesehen am 03.01.2023